2017
DOI: 10.1002/acm2.12091
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of AcurosXB source size setting for small intracranial targets

Abstract: This study details a method to evaluate the source size selection for small field intracranial stereotactic radiosurgery (SRS) deliveries in Eclipse treatment planning system (TPS) for AcurosXB dose calculation algorithm. Our method uses end‐to‐end dosimetric data to evaluate a total of five source size selections (0.50 mm, 0.75 mm, 1.00 mm, 1.25 mm, and 1.50 mm). The dosimetric leaf gap (DLG) was varied in this analysis (three DLG values were tested for each scenario). We also tested two MLC leaf designs (sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…reports the need to adjust source size for small field intracranial SRS using AcurosXB in the Eclipse planning system to avoid >10% central axis dose discrepancies for small target volumes. 20 When treating multiple targets distant from the isocenter, extra requirements are needed for setup accuracy and limitation of patient motion during treatment. To remove any patient rotation at setup, a 6DOF couch should be used for treatment.…”
Section: Ma Et Al Published a Planning Study Comparing Plans For Gammamentioning
confidence: 99%
“…reports the need to adjust source size for small field intracranial SRS using AcurosXB in the Eclipse planning system to avoid >10% central axis dose discrepancies for small target volumes. 20 When treating multiple targets distant from the isocenter, extra requirements are needed for setup accuracy and limitation of patient motion during treatment. To remove any patient rotation at setup, a 6DOF couch should be used for treatment.…”
Section: Ma Et Al Published a Planning Study Comparing Plans For Gammamentioning
confidence: 99%
“…Generally, adjustable parameters, such as the MLC parameters (i.e., dosimetric leaf gap (DLG) and MLC transmission factor (TF)) and focal spot size have attracted attention for the commissioning of RTPS. 3,[5][6][7][19][20][21] An important question is whether the uneven differences in VMAT calculated dose distributions could be compensated through the parameter adjustments or not. There are two concerns regarding this.…”
Section: Discussionmentioning
confidence: 99%
“…The 3% ΔD criterion was selected in this study because it is widely used, in combination with a range of Δd values, but the use of 3% as a ΔD criterion is not universal. Similarly, GAI values of 100% and 95% were selected as examples of extreme and commonly‐used PSQA action levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent surveys suggested that 3%/3 mm are currently the most commonly used gamma evaluation criteria, and the AAPM's task group report on IMRT commissioning (TG‐119) used 3%/3 mm and the AAPM's more recent task group report on modulated radiotherapy quality assurance (TG‐218) recommended 3%/2 mm. Investigations of cranial and extra‐cranial stereotactic radiotherapy have reported the use of 3%/2 mm, 3%/1.5 mm, 3%/1 mm and 3%/0.3 mm criteria.…”
Section: Methodsmentioning
confidence: 99%